If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -8) = 4(n + 2) Reorder the terms: 3(-8 + n) = 4(n + 2) (-8 * 3 + n * 3) = 4(n + 2) (-24 + 3n) = 4(n + 2) Reorder the terms: -24 + 3n = 4(2 + n) -24 + 3n = (2 * 4 + n * 4) -24 + 3n = (8 + 4n) Solving -24 + 3n = 8 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -24 + 3n + -4n = 8 + 4n + -4n Combine like terms: 3n + -4n = -1n -24 + -1n = 8 + 4n + -4n Combine like terms: 4n + -4n = 0 -24 + -1n = 8 + 0 -24 + -1n = 8 Add '24' to each side of the equation. -24 + 24 + -1n = 8 + 24 Combine like terms: -24 + 24 = 0 0 + -1n = 8 + 24 -1n = 8 + 24 Combine like terms: 8 + 24 = 32 -1n = 32 Divide each side by '-1'. n = -32 Simplifying n = -32
| (2n+5)(2n+3)=0 | | R=5x+43 | | (4g+7)+(7g+2)= | | 23+5x=14x-3 | | 4(c-3)+5=2c+3 | | 6(m+1)=3m-3 | | -3(a+4)=6 | | -g+6+2g=4g+4 | | 6x+7=2x-13 | | 12-1.7x=4.15 | | (x+1)+2(x-3)-5=(x+2)-(x+3)+2 | | ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) | | 3x+5=-6x+32 | | -2/5(5x-20y) | | 2x^2+8x+n=15+n | | -(ln)(2)/x=91.2 | | F(x)=x^4+6x^3+9x^2 | | x+7*2=122 | | x+7*2= | | 3n^2+4n-4=0 | | -4/3(33=n)=12=n | | 10x-30=10 | | x+2*(x+2+2x-8)=x+1*(x+1+2x-5) | | 14x-14-4+6=0 |